DEVELOPING A MODULE OF TEACHERS’ PROFESSIONALISM BASED EFFECTIVE TEACHERS’ THEORY - Danniarti, Rahma; Kristiawan, Muhammad; Tobari, Tobari (Sriwijaya University Learning and Education International Conference, 2018)
This study aimed at developing a module of teachers’ professionalism based effective teachers’ theory which valid, practical and effective. The development of this module used ADDIE Model. The research was conducted in SMP Negeri 7,15 and 35 Palembang. Data were collected through observation, interview, questionnaire, and test. The data were analyzed by using qualitative and quantitative approach. The results showed that teachers have started to know and understand how to manage the classroom effectively after they gain insight from the module on teachers professionalism based on effective teachers’ theory. The module was also valid, practical and effective after being tested.